Effect of anisole addition to waste cooking oil methyl ester on combustion, emission and performance characteristics of a DI diesel engine without any modifications. (15th October 2020) - Rajesh, A.; Gopal, K.; Melvin Victor, De Poures; Rajesh Kumar, B.; Sathiyagnanam, A.P.; Damodharan, D.
Highlights: Anisole was used as an oxygenated additive. Waste cooking oil is utilized in the diesel engine. Best blend composition were suggested in the study. Abstract: Energy recovery and utilization from waste presents an attractive alternative solution to compensate fossil fuel demands and reduces the risk of environmental hazards. The present study aims to investigate, the effect of increasing anisole fraction in the biodiesel extracted from waste cooking oil in a diesel engine. Tests were performed by blending anisole with waste cooking oil methyl ester up to 30% vol. and the results were compared with baseline diesel and biodiesel operation. The results reveal that, increasing the anisole content in biodiesel prolongs the ignition delay period. The in-cylinder pressure and heat release rate increase with higher anisole fraction. Among the test fuels, W90A10 blend shown 1.6% better BTE than biodiesel. The NOx emission was lowest when the engine is operated with W90A10 blend, at peak load, it decreased by 17% and 11% against diesel and biodiesel operation. The smoke opacity for neat biodiesel was highest and the addition of anisole suppressed the soot formation tendency of the biodiesel significantly. HC and CO emissions are generally high when the engine is operated with biodiesel. Blending anisole with biodiesel had a positive effect on both HC and CO emissions. From the findings, it is concluded that waste cooking oil methyl ester blended with 10% by vol. of anisole can be effectively utilized in diesel engine applications with lower emissions.